Analisis Gaya Kepemimpinan Dalam Meningkatkan Kinerja Karyawan PT. Sumbermulia Hasilguna Jakarta Selatan - Neng Indah Permatasari; Noto Susanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The aim of this research is to analyze leadership style in improving employee performance at PT. Sumbermulia Hasilguna Jakarta Branch. This research uses a qualitative method using SWOT analysis. This research was conducted at PT. Sumbermulia Hasilguna, South Jakarta. The data used in this research are interviews, observation and documentation. The leadership style used at PT Sumbermulia Hasilguna Jakarta is a democratic leadership style. It can be seen from several indicators that support this, namely that decision making is carried out through deliberation which involves other employees, and can accept suggestions and feelings from other employees so that they can make decisions more widely, are very responsible for their positions and there is no gap between leaders and employees. and the cooperation at PT Sumbermulia Hasilguna Jakarta branch is considered good and the impact of these results can be seen from the performance indicators, namely quality, quantity, use of time and cooperation, initiative from these four indicators, many employees complain about the lack of motivation for employees.